1996
DOI: 10.1111/j.1365-2648.1996.tb00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Using the diffusion of innovation model to influence practice: a case study

Abstract: There continue to be suggestions within the nursing literature that research findings are not being utilized in clinical practice. The reasons for this are well documented. However, less emphasis is given to ways to facilitate utilization. It seemed possible that non-utilization could be due not only to lack of knowledge, but also to the method of implementing change towards research-based practice. The "top-down', authoritarian, approach to dissemination of information within the NHS may have been a block to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Horsley et al . 1983, Hunt 1987, Pearcey & Draper 1996) there have been few studies which have evaluated interventions designed to promote research utilization, in nursing practice. Much can be learnt from the success and the failure of these projects.…”
Section: Discussionmentioning
confidence: 99%
“…Horsley et al . 1983, Hunt 1987, Pearcey & Draper 1996) there have been few studies which have evaluated interventions designed to promote research utilization, in nursing practice. Much can be learnt from the success and the failure of these projects.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the characteristics of Rogers' (2003) 'readily-adopted' innovation have been widely used as a basis for devising communication strategies to support the adoption of health care innovations (e.g., Becker, 1970a;Romano, 1990;Pearcey and Draper, 1996;Landrum, 1998;Hilz, 2000;Ash and Bates, 2005), though it has been criticized for providing insufficient guidance on how to design specific interventions to influence this process . The finding that twothirds of our sample does not adhere to Rogers' typology suggests one reason why such past guidance may have been insufficient, further suggesting both an alternative focus for the development of communication strategies, and that promoters of innovations may require different strategies based on innovation type.…”
Section: Discussionmentioning
confidence: 99%
“…The data were re-analysed excluding the fourth and fifth criteria, as few empirical studies of the models' effectiveness were identified in the published literature and little variation in the scoring of the generalisability criterion was noted in the ratings. Table 2 shows the results for the top 8 rated models in the analyses, [8][9][10][11][12][13][14][15] with the mean total scores for the 5 criteria and the 3 core criteria (clear and concise, comprehensive, and ease of use by direct care nurses).…”
Section: Selecting An Ebp Model For Nursingmentioning
confidence: 99%